2019
DOI: 10.3390/polym11091490
|View full text |Cite|
|
Sign up to set email alerts
|

Facile Functionalization via Plasma-Enhanced Chemical Vapor Deposition for the Effective Filtration of Oily Aerosol

Abstract: With the growing concern about the health impacts associated with airborne particles, there is a pressing need to design an effective filter device. The objective of this study is to investigate the effect of plasma-based surface modifications on static charges of electrospun filter media and their resulting filtration performance. Polystyrene (PS) electrospun web (ES) had inherent static charges of ~3.7 kV due to its electric field-driven process, displaying effective filtration performance. When oxygen speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

6
3

Authors

Journals

citations
Cited by 14 publications
(25 citation statements)
references
References 49 publications
(64 reference statements)
0
25
0
Order By: Relevance
“…With the growing environmental concern with the airborne particulate matters (PM), various filter materials are being explored in search of adsorbate specificity, high filtration performance, environmental sustainability, etc. [10,11,22,25]. Most of those studies focus on achieving the high filtration efficiency, but lack the understanding of material properties that make the robust electret filters in consideration of charge retention.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With the growing environmental concern with the airborne particulate matters (PM), various filter materials are being explored in search of adsorbate specificity, high filtration performance, environmental sustainability, etc. [10,11,22,25]. Most of those studies focus on achieving the high filtration efficiency, but lack the understanding of material properties that make the robust electret filters in consideration of charge retention.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that the exposure of an electret filter to heat, humidity, and solvent can cause deterioration of filtration performance, as a result of charge loss [17,22,24].The environmental factors that deteriorate the electret filtration have been studied rather frequently [8,17,18,24], probably because it is associated with the practical use conditions; on the other hand, the material aspects that influence the charge decay have rarely been studied. While various material options were examined to attain the high-quality factor filters [10,25,26], it lacked scrutiny on the material attributes that enable the long-term charge retention. Moreover, the dielectric constant (ε r ) of material has rarely been associated with the charge decay phenomenon in experimental investigation [1,27], while there are implications that ε r is related with the charge stability and conductivity [7,27,28].The purpose of this work is to investigate the polymeric attributes that influence the charge retention capacity of electret filters.…”
mentioning
confidence: 99%
“…For the solid aerosol, the loading trends can differ by the filter characteristics. For the porous electret filter that allows depth loading, penetration initially increases as the charged surface is masked by the deposition of solid particles; then after reaching the maximum penetration, the penetration begins to decrease as the solid particles clog the pores of the filter material [ 30 , 31 , 32 ]. The resistance may build up more quickly after reaching the maximum penetration, as the pores of the filter are clogged.…”
Section: Filtration Performance Of Fiber-based Filters For Particumentioning
confidence: 99%
“…To attach the oxygen group to the composite surface, the composite fabric was subject to an O 2 plasma treatment for 5 min at 200 W with 160 cm 3 /min in the plasma system (COVANCE, FemtoScience, Hwaseong, South Korea) [41]. To coat the surface with the fluorinated compound by the plasma-enhanced chemical vapor deposition (PECVD), the composite fabric was treated under C 4 F 8 gas for 25 min at 200 W with 100 cm 3 /min [42,43]. The generated frequency of plasma was 50 kHz in both O 2 and C 4 F 8 plasma processes.…”
Section: Fabrication Of Ml/pvdf and Ml/panmentioning
confidence: 99%